2023
DOI: 10.1007/s10725-023-01064-3
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride stress affects seed germination and seedling growth by altering the morpho-physiology of an African local bean variety

Sara Chahine,
Sara Melito,
Vittoria Giannini
et al.

Abstract: Increased fluorine pollution represents a serious limitation for the productivity of important crops such as beans. The present study was conducted to detect antagonistic/synergistic ion mobility during seed germination in the presence of F contamination (KF and NaF). NaCl was used as a benchmark. The results showed that germination of Jesca, an African (Tanzania) bean variety, significantly dropped with high F levels (10% KF and 3% NaF). High F levels reduced Jesca growth and decreased root and shoot biomass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…This shows that inoculating with P. aeruginosa strain PAR helps to lessen the negative impacts of NaF on seed germination, presumably through mechanisms like increased nutrition availability or stress tolerance induction. Chahine et al (2023) reported that Jesca (African-Tanzania bean variety) seed germination considerably declined with higher levels of fluorides (3% NaF and 10% KF). Pelc et al (2020) found that an upsurge in the fluoride concentration decreased seed germination, both in the roots and embryos of all tested cultivars of winter wheat.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This shows that inoculating with P. aeruginosa strain PAR helps to lessen the negative impacts of NaF on seed germination, presumably through mechanisms like increased nutrition availability or stress tolerance induction. Chahine et al (2023) reported that Jesca (African-Tanzania bean variety) seed germination considerably declined with higher levels of fluorides (3% NaF and 10% KF). Pelc et al (2020) found that an upsurge in the fluoride concentration decreased seed germination, both in the roots and embryos of all tested cultivars of winter wheat.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is critical to comprehend the practical implications of adopting P. aeruginosa strain PAR as a bioinoculant in fluoride-contaminated areas for sustainable agriculture. According to Chahine et al (2023) , high fluoride concentration reduced the growth and root-shoot biomass (95% and 50% with NaF and KF, respectively) of Jesca. Zulfiqar et al (2023) reported that fluoride toxicity was reduced using fluoride-resistant bacterial strains (SS-10a and SS-5a) in the soil.…”
Section: Discussionmentioning
confidence: 99%